Pengaruh Profitabilitas dan Beban Pajak Tangguhan terhadap Penghindaran Pajak: Studi Kasus pada Perusahaan Infrastruktur yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2022 - Mellisa Karen Benedicta; Joan Yuliana Hutapea (VISA: Journal of Vision and Ideas, 2024)
This research is intended as an effort to evaluate the impact of an organization's profits and retribution costs which are recognized as being related to the tendency of foundation organizations listed on the Indonesian Stock Exchange to avoid costs during the 2018-2022 period. Seven companies were selected as samples from a total of 67 companies using a purposive sampling approach technique. This research was tested using descriptive statistical techniques, examination of classical assumptions, and multiple linear regression analysis to test the research hypothesis. The results of the t-test statistical test indicate that there is a mathematically significant correlation between tax avoidance practices and the level of profitability, with a significance level of 0.004. However, there are no significant implications of the existence of deferred tax expenses on tax avoidance practices, as reflected at the significance level of 0.110. By referring to the results of the coefficient of determination analysis, it can be proven that profitability and simultaneously, deferred tax expenses have a significant influence on tax avoidance strategies, reaching 23.3%.